Feeding Problems Are Persistent in Children with Severe Congenital Hyperinsulinism - Banerjee, Indraneel; Forsythe, Lynette; Skae, Mars; Avatapalle, Hima Bindu; Rigby, Lindsey; Bowden, Louise E.; Craigie, Ross; Padidela, Raja; Ehtisham, Sarah; Patel, Leena; Cosgrove, Karen E.; Dunne, Mark J.; et al. (Frontiers in Endocrinology, 2016)
Background: Congenital Hyperinsulinism (CHI) is a rare but severe disorder of hypoglycaemia in children, often complicated by brain injury. In CHI, the long term prevention of hypoglycaemia is dependent on reliable enteral intake of glucose. However, feeding problems often impede oral glucose delivery, thereby complicating the management of hypoglycaemia. Feeding problems have not been systematically characterised in follow up in a cohort with CHI. Aims: We aimed to determine the prevalence, types and persistence of feeding problems in a cohort of children with CHI and investigate potential causal factors. Methods: Feeding problems were defined as difficulty with sucking, swallowing, vomiting and food refusal (or a combination) in an observational study in 83 children in a specialised CHI treatment centre. The prevalence of feeding problems at diagnosis, 6 and 12 months after diagnosis were noted. Genetic mutation status and markers of severity of CHI were tested for association with feeding problems. Results: A third of children with CHI had feeding problems (n=28), of whom 93% required antireflux medication and 75% required nasogastric and gastrostomy tube feeding. Sucking and swallowing problems were present at diagnosis but absent later. Vomiting was present in 54% at 6 months, while food refusal was present in 68% at 6 months and 52% at 12 months. The age at commencing and stopping nasogastric tube feeding did not correlate with feeding problem frequency at 6 and 12 months. Children with feeding problems had severe hypoglycaemia at diagnosis and required glucagon infusion more often [odds ratio (OR) (95% confidence intervals) (95%CI) 28.13(2.6-300.1), p=0.006] to normalise glucose levels. Feeding problems were more frequent in those with diffuse CHI undergoing subtotal pancreatectomy [n(%)=10(35%) v 0(0%), p<0.001], in contrast to those with spontaneous resolution [6(22%) v 32(58%), p=0.002]. Those undergoing focal lesionectomy also had reduced feeding problems at 6 months after diagnosis [OR (95%CI) 0.01(0.0-0.2), R2=0.42, p=0.004]. These observations suggest that persistence of hyperinsulinism was associated with feeding problems. Conclusions: Feeding problems occur in a significant proportion of children with CHI. Severe hyperinsulinism, rather than nasogastric tube feeding or medications, is the main factor associated with feeding problems.